Musical AKAs: Assumed Names and Sobriquets of Composers, Songwriters, Librettists, Lyricists, Hymnists, and Writers on Music (Book Review) - Guise, Janneka L. (CAML Review / Revue de l’ACBM, 2010)
[no abstract]